Sustainability of community-based domestic water systems in Janiuay, Iloilo. - Fabila, Nozel Christy A.
Access to water for domestic use is limited in most rural areas in the Philippines. To address this, the government funds the construction of Level II water systems in rural areas through the Kapit Bisg Laban sa Kahirapan-Comprehensive Integrated Delivery of Social Services (KALAHI-CIDSS) program, which is turned over to recipient communities with the expectation that they will be operated and maintained by community-based organizations (CBO). In Panay, 94 water systems have been funded by the KALAHI-CIDSS. However, some of these water systems have not been sustained. This study analyzes the conditions that allow collective action among members of CBOs to sustain their water system. The paper used an integrated theory of the Common Pool Resource (CPR) theory and Goal Framing Theory. Through a multi-method comparative study of three KALAHI-CIDSS-funded barangay water systems in Janiuay, Iloilo, it is argued that the institutional design of the CBO and the collective orientation of the members affect the collective action of members. The findings reveal that CBOs that were able to sustain their water system had all the elements of the CPR theory coupled with members having a normative goal frame. The results suggest that participative rule-making, membership benefits, and participative local government support were factors that affected promotion of collective action among members.